Contribution Succinonitrile Additive for Performa LiTFSi Solid Polymer Electrolytes for Li-Ion Battery - Qolby Sabrina; Titik Lestariningsih; Christin Rina Ratri; Achmad Subhan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
The purpose of this study is to evaluate the performance of Solid Polymer Electrolyte (SPE) which has the role of replacing liquid electrolyte in the battery system to reduce leakage. Evaluation of electrochemical SPE consisted of mixture lithium salt, solid plasticizer, and polymer precursor with different ratio. Impedance spectroscopy was used to investigate ionic conduction and dielectric response lithium bis(trifluoromethane)sulfony imide (LiTFSI) salt, and additive succinonitrile (SCN) plasticizer. The result showing enhanced high ionic conductivity. In half-cell configurations, wide electrochemical stability window of the SPE has been tested. The great potential of SPE for applications in lithium-ion batteries can be seen from the ability of window stability at room temperature. Additive SCN contributes to forming pores that make it easier for the Li-ion to move from the anode to the cathode and vice versa for better perform SPE. Pore of SPE has been characterization with FE-SEM. Additive 50% w.t SCN shows the best ionic conductivity with 4.2 volt wide stability window and pretty much invisible pores.